Assessment of factors affecting the decision of smallholder farmers to use alternative maize storage technologies in Gatsibo District-Rwanda - Benimana, Gilberthe Uwera; Ritho, Cecilia; Irungu, Patrick (Elsevier, 2021)
Storage is an important aspect of food security in developing countries. Therefore, it is crucial for farmers to have access to sustainable storage technologies to cope with storage losses. Maize is an important staple and commercial food in Rwanda, but maize farmers are still being challenged by storage losses because of the lack of proper storage facilities. It is in that regard that advanced maize storage technology, notably hermetic maize storage technology, has been introduced in Rwanda in 2012. However, since its introduction, the adoption rate is low among smallholder maize farmers. Understanding the factors influencing farmers’ choice of alternative maize storage technology could provide Rwandan policymakers with important information for designing policies and programs aimed at reducing maize post-harvest losses to enhance household food security. This study used a multivariate probit model on a randomly selected cross-sectional sample of 301 smallholder maize farmers from the Gatsibo District of Rwanda to take part. The results revealed that the common maize storage technologies used among smallholder farmers were polypropylene sacks with and without chemicals, hermetic bags, and silos. Only 41% of respondents used hermetic maize storage technology. The model results showed that membership in a farmer group, access to credit, the quantity of maize produced, access to training, and selling maize soon after it dries, were the major factors influencing the decision of smallholder farmers to use alternative maize storage technologies. The study recommends that the policymakers and other stakeholders in post-harvest loss reduction should support the dissemination of advanced storage technologies to facilitate access. The government should support farmer acquisition of post-harvest maize loss reduction technologies either through subsidization of hermetic bags or provision of cheap credit.